Reference and information services an introduction - Smith, Linda C.; Wong, Melissa Autumn (Library and information science text series, 2016)
"Thoroughly updated, this go-to work links you--and though you, your patrons--to the significant changes that have occurred in reference and information sciences thanks to the growth in digital content"--Provided by publisher.